Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376361
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Stimulation Needs in Dementia Care through Wall-Sized Displays

Abstract: Beside reminiscing, the increasing cognitive decline in dementia can also be addressed through sensory stimulation allowing the immediate, nonverbal engagement with the world through one's senses. Much HCI work has prioritized cognitive stimulation for reminiscing or personhood often on small screens, while less research has explored sensory stimulation like the one enabled by large displays. We describe a year-long deployment in a residential care home of a wall-sized display, and explored its domestication t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 100 publications
2
20
0
Order By: Relevance
“…Another example is that activities should be multimodal. Similarly to other works [24,54,66], we found that visual cues and music contributed to engaging people living with dementia in social interaction. However, our indings are grounded in the use of a digital app that was installed on a tablet device.…”
Section: Facilitation As a Shared Task Between Humans And Technologiessupporting
confidence: 86%
“…Another example is that activities should be multimodal. Similarly to other works [24,54,66], we found that visual cues and music contributed to engaging people living with dementia in social interaction. However, our indings are grounded in the use of a digital app that was installed on a tablet device.…”
Section: Facilitation As a Shared Task Between Humans And Technologiessupporting
confidence: 86%
“…Accordingly, technologies for dementia are re-conceptualized to focus on individual potential and possibility rather than the loss of skills or abilities [4,65,66,78]. This ongoing body of work has resulted in numerous prototype developments [38,49,53,92,107] and ethnographic evaluations in residential care settings [36,66,78,79] and motivated Experience-Centered Design research for people with dementia in HCI [35,38,78,109]. These works promote socially inclusive practice [12,48,104], empowerment and agency [38,74,106,110] and a sense of self and identity [4,58,66,78,109].…”
Section: Background 21 Dementia In Hcimentioning
confidence: 99%
“…This body of research has shifted perspectives of people with dementia from addressing perceived cognitive and physical disabilities to acknowledging them as individuals with unique lived experiences [4,66,78,109]. Therefore, there is an increased research interest in technologies that enrich subjective experiences by offering sensory stimulation [49,54,92], enabling people with dementia to make social contributions in their environment [38,79,110], and exploring and maintaining selfhood and identity [4,66,108,109].…”
Section: Introductionmentioning
confidence: 99%
“…Their system not only presented activation content, but also attempted to moderate its presentation. Sas et al [38] use wall-sized display as alternative way for content presentation (with a focus on sensory stimulation) on a large scale and could show a high engagement. Some activation systems use music or tangible devices to create activation paradigms which stimulate many senses.…”
Section: Technical Systems For Activation Of People With Dementiamentioning
confidence: 99%